A review: improved iron and zinc contents in rice through biofortification techniques / Raihana Nadhirah Mohd Zahid - Mohd Zahid, Raihana Nadhirah (Faculty of Plantation and Agrotechnology, 2019)
Rice (Oryza sativa) is the staple crop for half of the world’s population. Most of peoples especially in East and Southeast Asia are depend on rice as their dietary intake. However, rice is lack of essential micronutrient especially Iron (Fe) and Zinc (Zn). Both Fe and Zn have important functions in human health. People will affect by some health problems such as slower growth, lower IQ, malnutrition and death, if they do not have sufficient micronutrient in their diet. The most affected people are children, women and pregnancy women in poor population. The objectives of study are to review on enhancing nutrient contents especially Fe and Zn in rice to alleviate health problem among people and to review on improving the quality, quantity and nutrition of rice in future. There are lot of strategies to improve Fe and Zn in rice such as through biofortification. There are three approaches of biofortification such as agronomic practices, conventional breeding, and transgenic strategies. Agronomic practices have two methods to improve Fe and Zn which is through fertilizer application in the soil and through foliar application directly to the leaves of the rice. Conventional breeding is the development or improvement of cultivars using conservative tools for manipulating plant genome within the natural genetic boundaries of the species. Meanwhile, transgenic strategies is rice contain foreign gene to get the better characteristics of rice. Thus, biofortification techniques is the best strategy to supply an adequate Fe and Zn content in rice to increase the quality of rice in future as well as can improve nutrients in human dietary.